GANTI RUGI TERHADAP KORBAN KECELAKAAN LALU LINTAS YANG MENGALAMI CACAT FISIK DI TINJAU DARI ASPEK HUKUM PERDATA - Khairunnisah, Nanda Theresia dan (Universitas 17 Agustus 1945 Samarinda, 2019)
Legal rules often focus on punishing criminals but victims also need to be considered because victims are the parties who are sufficiently disadvantaged and suffer. Everyone thinks that the best way to help the victim is to catch the criminal, as if the criminal is the only source of trouble for the victim in the traffic accident. This is the background of the author taking the title Compensation Against Traffic Accident Victims Who Have Physical Disabilities In Review Of Civil Aspects. The method used in this study is normative legal research. Conclusions from the formulation of the problem taken in terms of compensation efforts based on Article 1365 of the Civil Code reads